Impact of polymorphisms of pharmacokinetics‐related genes and the inflammatory response on the metabolism of voriconazole. Issue 2 (23rd February 2022) - Aiuchi, Naoya; Nakagawa, Junichi; Sakuraba, Hirotake; Takahata, Takenori; Kamata, Kosuke; Saito, Norihiro; Ueno, Kayo; Ishiyama, Masahiro; Yamagata, Kazufumi; Kayaba, Hiroyuki; Niioka, Takenori
Abstract: The effects of inflammatory responses and polymorphisms of the genes encoding cytochrome P450 (CYP) ( CYP2C19 and CYP3A5 ), flavin‐containing monooxygenase 3 ( FMO3 ), pregnane X receptor ( NR1I2 ), constitutive androstane receptor ( NR1I3 ), and CYP oxidoreductase ( POR ) on the ratio of voriconazole (VRCZ) N ‐oxide to VRCZ (VNO/VRCZ) and steady‐state trough concentrations (C0h ) of VRCZ were investigated. A total of 56 blood samples were collected from 36 Japanese patients. Results of multiple linear regression analyses demonstrated that the presence of the extensive metabolizer CYP2C19 genotype, the dose per administration, and the presence of the NR1I2 rs3814057 C/C genotype were independent factors influencing the VNO/VRCZ ratio in patients with CRP levels of less than 40 mg/L (standardized regression coefficients (SRC) = 0.448, −0.301, and 0.390, respectively; all p  < .05). With regard to the concentration of VRCZ itself, in addition to the above factors, the presence of the NR1I2 rs7643645 G/G and rs3814055 T/T genotypes were found to be independent factors influencing the VRCZ C0h in these patients (SRC = −0.430, 0.424, −0.326, 0.406 and −0.455, respectively; all p  < .05). On the contrary, in patients with CRP levels of at least 40 mg/L, no independent factors were found to affect VNO/VRCZ and VRCZ C0h . Inflammatory responses, and CYP2C19 and NR1I2 polymorphisms may be useful information for the individualization of VRCZ dosages. Abstract : Both the CYP2C19 polymorphism and the status of the inflammatory response affect the N ‐oxidation pathway, the major metabolic pathway of voriconazole. Therefore, the usefulness of CYP2C19 genotype analysis in the individualization of voriconazole dosages depends on the state of the patient's inflammatory response. In addition, the NR1I2 rs3814057 polymorphisms may also be useful in predicting voriconazole N ‐oxide/voriconazole.